Intercultural sensitivity in Orientalist cinema. Issue 2 (1st August 2020) - Mather, Philippe
Edward Said's dogmas of Orientalism are a succinct summary of western perceptions of the East, which reveal an essentially racist discourse that also speaks to the westerner's self-perception. While there is a tendency in fiction film to polarize attitudes as either friendly or hostile, for reasons of narrative economy and to enhance dramatic conflict, this article argues that it is possible to measure the behaviour of fictional characters on a continuum describing intercultural sensitivity to assess how these characters appear to respond to the idea of cultural differences, broadly ranging from the most ethnocentric views to more ethnorelative ones. Since the intercultural development continuum (IDC) is structured as five developmental stages, it provides a finer psychological template than Orientalist binaries, offering a more nuanced view of character motivations and attitudes. The IDC scale is ideally suited to narrative analysis as it usefully describes successive stages that characters may exhibit throughout the course of a story depicting intercultural exchanges. The IDC allows the analyst to gauge the degree of conformance of any given film to Said's aforementioned dogmas, particularly those films that either express an ambivalent attitude or appear superficially more enlightened or accommodating of difference. This model will be illustrated with a number of case studies selected from a filmography focusing on western representations of Singapore in film and television, from 1940 to 2015, including titles such as the Bette Davis plantation melodrama The Letter, the science fiction thriller Hitman: Agent 47 and the Australian period TV series Serangoon Road.